2018
DOI: 10.4018/ijcrmm.2018040101
|View full text |Cite
|
Sign up to set email alerts
|

How Customer Relationship Management (CRM) and Innovation Influence Business Performance Mediating Role of Innovation

Abstract: According to Bain & Company, CRM is at the top of management tools in recent years. This article aims to answer the productivity paradox of CRM and investigates the impact of both CRM and innovation on firm performance and also investigating mediating role of innovation to explain the effect of CRM on performance. To obtain research objective, an empirical study was conducted. For evaluating conceptual model, survey instrument was developed. The relationship between dimensions of CRM and innovation, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Moreover, innovation is related to the firm's ability to search for novel and optimum ways for identifying, acquiring and establishing organizational tasks (al-Ansari et al, 2013; Chang et al, 2017). In this regard, a significant positive relationship exists between SMEs innovative dimension and the performance of business (Pour, 2018).…”
Section: Crm As An Innovationmentioning
confidence: 99%
“…Moreover, innovation is related to the firm's ability to search for novel and optimum ways for identifying, acquiring and establishing organizational tasks (al-Ansari et al, 2013; Chang et al, 2017). In this regard, a significant positive relationship exists between SMEs innovative dimension and the performance of business (Pour, 2018).…”
Section: Crm As An Innovationmentioning
confidence: 99%
“…A few empirical studies have investigated how this is achieved [21]. Pour et al [28] aimed to investigate the impact of customer relation capabilities on innovation capabilities as dynamic capabilities, the findings of their study indicated to the direct impact of customer relation capabilities on innovations capabilities. In Brazil, Toriani and Angeloni [29] found that use of IT customer relationships management capabilities can support knowledge capabilities as dynamic capabilities.…”
Section: B Social Media Dynamic Capabilities and Operationalmentioning
confidence: 99%
“…This flexibility will help retailers collect and analyze service information through market knowledge, recognize new opportunities, and thus maintain customized services and long-term relationships with customers (Li, Dong, Ota, & Guo, 2016;Meyer, Gonzalez Hernandez, & Toldos Romero, 2016;Mirica, 2019;Popescu & Ciurlău, 2019). Innovation management of the critical factors in efficient CRM systems improves customer service, identify new products, and reduces customers' escape (Pour, Mamani, & Rahimzadeh, 2018;Wang, Yang, Wang, Sherratt, & Zhang, 2020). Also, online retailing through CRM identifies competitive information and can turn it into an opportunity for further development (Algharabat, 2014;Budler & Trkman, 2019).…”
Section: Introductionmentioning
confidence: 99%